2003
DOI: 10.1115/1.1537253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unsteady Wake Passing Frequency on Boundary Layer Transition, Experimental Investigation, and Wavelet Analysis

Abstract: Detailed experimental and theoretical investigations were carried out to study the effect of unsteady wake passing frequency on the boundary layer transition along the concave surface of a curved plate under a zero longitudinal pressure gradient. Periodic unsteady flow with different passing frequencies is generated utilizing an unsteady flow research facility with a rotating cascade of rods positioned upstream of the curved plate. Extensive unsteady boundary layer measurements are carried out. The data are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Indeed, there is a lot of experimental evidence that wake turbulence induced bypass transition happens in a quasi-steady way. We refer to the work of Addison and Hodson [2,3], Orth [28], Liu, Rodi and co-workers [7,18], Schobeiri et al [36]. In these experimental works, it is shown that bypass transition caused by wake impingement begins at the same location, independent of the wake passing frequency.…”
Section: Equation For Near-wall Intermittency Factor γmentioning
confidence: 93%
“…Indeed, there is a lot of experimental evidence that wake turbulence induced bypass transition happens in a quasi-steady way. We refer to the work of Addison and Hodson [2,3], Orth [28], Liu, Rodi and co-workers [7,18], Schobeiri et al [36]. In these experimental works, it is shown that bypass transition caused by wake impingement begins at the same location, independent of the wake passing frequency.…”
Section: Equation For Near-wall Intermittency Factor γmentioning
confidence: 93%
“…The wake recovery was complete at low Strouhal numbers but reduced with increase in the wake passing frequency. Another similar study by Shobeiri et al [29] conducted tests on a concave plate with an upstream squirrel cage type wake generator. Such a setup is shown to have realizable multi-stage wake replications due to opposing directions of moving wakes, though too large a wake Strouhal number will cause the opposing wakes to combine and increase free-stream turbulence intensity.…”
Section: Review Of Literaturementioning
confidence: 93%
“…Schobeiri and his co-workers also extended the theoretical work by Schobeiri et al (1995a) to a relative frame of reference to explain the development and decay of unsteady wakes. Schobeiri et al (1995b) experimentally investigated the effects of periodic unsteady wake passing frequency on the boundary layer transition and its development along the concave surface of a constant curvature plate at zero pressure gradient. In a continuing effort, Schobeiri et al (1998) presented a detailed experimental study of the behavior of the unsteady boundary layer of a turbine cascade with a chord length of c = 281.8 mm.…”
Section: Background: Unsteady Boundary Layer Transitionmentioning
confidence: 99%